Charge transition phenomena in the heterostructure crystalline Si-Bi-amorphous film Ge₃₃As₁₂Se₅₅ - Kondrat, O.; Popovich, N.; Dovgoshej, N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Ge₃₃As₁₂Se₅₅-Si(n) heterostructures with modified by bismuth atoms transition layer were obtained by the discrete thermal evaporation method. Described are formation and investigation methods for these heterostructures. The mechanism of charge transmission in this heterostructures was ascertained. It is illustrated that the barrier for holes at the boundary is absent. The energy diagram of the heterostructure was built. Analyzed is the absence of a soft breakdown, which is caused by the electrons transfer through interstices when the negative voltage is applied. The dependence of heterostructure electrophysical properties on Ge₃₃As₁₂Se₅₅ film thickness was investigated. It is shown that in heterostructures with a modified transition layer ther is a necessity to use Ge₃₃As₁₂Se₅₅ film with the thickness more than 0.4 mm. It is ascertained that at the modification of the transition layer the conversion from the sharp to smooth transition takes place, which is caused by diffusion of bismuth atoms to surface layers.